2009
DOI: 10.1111/j.1365-2796.2008.02016.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between lipoprotein components and risk of ischaemic and haemorrhagic stroke in the Apolipoprotein MOrtality RISk study (AMORIS)

Abstract: Objectives. To compare lipoprotein components associated with ischaemic and haemorrhagic stroke by age and gender in the Apolipoprotein MOrtality RISk (AMORIS) Study (n = 148 600).Design. Prospective follow-up study (11.8, range 7-17 years) of fatal and nonfatal ischaemic and haemorrhagic stroke through linkage with Swedish hospital discharge and mortality registers.Setting. Measurements of lipoprotein components from health check-ups in the larger Stockholm area.Results. Ischaemic stroke was more common than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 47 publications
(77 reference statements)
9
57
1
6
Order By: Relevance
“…Additional results (55) also favor apoB over LDL-C, and others are also reported in the section on the apo-ratio below. Such major studies are the AMORIS (3,44,56,57). In our study we found the steepest risk-relationship for MI with increasing values of apoB followed by non-HDL-C and the lowest increase in relation to LDL-C values with similar risk progressions for men and women (Figure 2 and Figure 3 left).…”
Section: Apob Versus Ldl-c and Risk For CV Eventssupporting
confidence: 60%
“…Additional results (55) also favor apoB over LDL-C, and others are also reported in the section on the apo-ratio below. Such major studies are the AMORIS (3,44,56,57). In our study we found the steepest risk-relationship for MI with increasing values of apoB followed by non-HDL-C and the lowest increase in relation to LDL-C values with similar risk progressions for men and women (Figure 2 and Figure 3 left).…”
Section: Apob Versus Ldl-c and Risk For CV Eventssupporting
confidence: 60%
“…213 In the Diabetes Epidemiology: Collaborative analysis Of Diagnostic criteria in Europe (DECODE) study, non-HDL-C predicted 10-year CVD mortality only among those with impaired fasting glucose, not among those with normal fasting glucose. 214 Non-HDL-C levels also predicted ischemic stroke, 215,216 and its predictive value has been further demonstrated in both men and women, across all age and ethnic groups, and with or without CVD or associated risk factors. Non-HDL-C can be assessed in the nonfasting state 22,217 and is more accurately determined because it does not depend on fasting triglyceride concentrations, as calculated LDL-C does.…”
Section: Non-hdl-cmentioning
confidence: 99%
“…[203][204][205][206][207][208][209][210][211][212][213][214][215][216] In the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) Study, an autopsy study of 15-to 34-year-old individuals who died of non-CVD causes, non-HDL-C was correlated with fatty streaks and raised lesions in the right coronary artery. 204 In adults, non-HDL-C correlates with coronary calcification 205,206 and CVD progression.…”
Section: Non-hdl-cmentioning
confidence: 99%
“…This linkage of national registers to the CALAB database is called the Apolipoprotein MOrtality RISk (AMORIS) study, and it has been described in detail elsewhere. [15][16][17][18][19][20][21] Our study complied with the Declaration of Helsinki, and the ethics review board of the Karolinska Institute approved the study.…”
Section: Study Populationmentioning
confidence: 99%